2014
DOI: 10.1063/1.4866337
|View full text |Cite
|
Sign up to set email alerts
|

Work function tuning of metal/graphene stack electrode

Abstract: Articles you may be interested inErratum: "Work function tuning and improved gate dielectric reliability with multilayer graphene as a gate electrode for metal oxide semiconductor field effect device applications" [Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Internal photoemission (IPE) spectroscopy [45], low-energy electron microscopy (LEEM) [44,46], scanning tunneling microscopy (STM) [47], scanning photocurrent microscopy (SPCM) [9], and capacitance-voltage (C-V) measurements using a metalgraphene semiconductor capacitor structure [48,49] are other methods used worldwide for measuring the WF of graphene.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal photoemission (IPE) spectroscopy [45], low-energy electron microscopy (LEEM) [44,46], scanning tunneling microscopy (STM) [47], scanning photocurrent microscopy (SPCM) [9], and capacitance-voltage (C-V) measurements using a metalgraphene semiconductor capacitor structure [48,49] are other methods used worldwide for measuring the WF of graphene.…”
Section: Other Methodsmentioning
confidence: 99%
“…The interesting finding here is that the effect of metal contact on the WF of graphene varied for graphene layers with different thicknesses. Song et al reported that tuning the WF of graphene in contact with metal from 4.3 eV to 5.1 eV could be achieved by changing its thickness [48]. They showed that the WF of SLG was easily affected by the WF of the metal contact, while that of FLG was less sensitive ( Figure 3c).…”
Section: Doping Graphene Layers With Different Thickness Was Investigmentioning
confidence: 99%
“…Calculations are carried out using the preferred functional in the case of adsorption energy, LDA, for the A configuration. The WF of monolayer graphene is calculated to be 4.52 eV, which is under the measured value of ~ 5 eV by Song et al As they also reported, it is considerably affected by metal contacts [45]. The results clearly show that WF of NMCs is larger than that of graphene.…”
Section: Physisorption Interfacementioning
confidence: 69%
“…32 Despite charge transfer and the development of a built-in potential, its magnitude (and that of the work-function change) can be expected to be small for the scenario of a one to two monolayers of graphene deposition. Studies, for example by Song et al, 33 point to relatively small work-function changes. Thus it remains unclear why the modest shifts might cause large changes in SEY values from over 1.0 for pure copper, as reported.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%